Obrazy rodziców w poradnikach dla nauczycieli. Raport z badań wstępnych - Beata Adrjan (Problemy Wczesnej Edukacji)
The article attempts to identify the images of parents presented in the selected teachers’ guides. Based on a content analysis of these guides, the author identified two ways of presenting parents: first portraying parents as difficult, demanding and confrontational, and second presenting them as partners of the school. The conducted analysis also shows two approaches to building relationships between teachers and parents: first based on a strategy of conflict and confrontation with parents, and second based on a positive attitude towards parents and a joint work of teachers and parents for the benefit of children. In conclusions the author attempts to search for the hypothetical contexts of constructing the images of parents and their relationships with the school presented in the teachers’ guides.